Implementasi Kurikulum Tingkat Satuan Pendidikan (KTSP) Bahasa Arab Di MAN Tembilahan Indragiri Hilir Riau - Nur Komariah (Al-Afkar : Jurnal Keislaman & Peradaban, 2014)
KTSP is the result of innovation from KBK. In the KTSP the teacher have to reach the professionalism of listening competence , speakng competence, reading competence, and writing competence, that supported with the creation of an active environment, creative, effective and fun. Islamic Junior High School of Tembilahan is one of the school that teach Arabic and implemented the KTSP but in the implementation there are some competencies that have not owned by their students. This is due to the background of Arabic language teachers who are not of Arabic language teacher education plus the background of the different students differently. This is because of the education background of the teacher was not from Arabic education and also the background of the students was different.